Measuring student attitude and knowledge in technology-rich biology classrooms - Incantalupo, L.; Treagust, David; Koul, Rekha (Springer, 2013)
The use of technology in schools is now ubiquitous, but the effectiveness on the learning environment has mixed results. This paper describes the development and validation of an instrument to measure students’ attitudes toward and knowledge of technology with the aim of investigating any differences based on gender after a course where the science department made use of technology as an integral part of teaching biology. In this study, conducted in one school in the state of New York, in the United States of America, the Students’ Attitudes Toward and Knowledge of Technology Questionnaire was administered to nearly 700 high school science students. A principal component and principal factor analysis resulted in new scales from the validation of the instrument that demonstrated high reliabilities. There were statistically significant gender differences in all the scales of the questionnaire in favor of males.